Competence of university teachers: perception of the students, the experts and the own protagonists - Óscar Mas Torelló (Universitat Politècnica de València, 2012)
Higher education institutions are experiencing one of the greatest moments of transformation in its history, especially caused by the implementation of the European Higher Education Area. The changes caused in the context where the university professor develop their work, causing changes in their functions, roles and tasks, leading the need to develop new competencies to pay attention correctly their professional functions. This new job scene, these new demands have generated new training requirements to the university teachers. To address the satisfaction of these new training needs, to establish appropriate protocols concerning accreditation, selection, promotion and training the university teachers, the new competence profile must be defined to develop satisfactorily their teacher, researcher and manager function, considering different works scenarios. To define the competence profile of the university professor has made descriptive research that combines quantitative and qualitative methodologies, different techniques (questionnaires, interviews, focus groups and Delphi technique) and information sources (teachers, experts and students). In this article, we only going to work with the data obtained from different informants (students, teachers and experts) about the professors' competences (design, development, tutoring, assessment, quality improvement and participation), but we are not going to present the data of the 34 units of competence that make up this profile, and we are not going to present the data of the competences and units of competence of the professor's research function. The results obtained help us to establish training priority areas and the needs to develop each competence unit according to the stages of professional development.